Quantifying the Boiling Point: A Distributed Lag Non-Linear Analysis of Heatwave Intensity and the 'Thermal Distress' Threshold for Psychiatric Morbidity in an Indonesian Metropolis - Taufiq Indera Jayadi; Eva Naritawati; Nurul Hanifah; Maximillian Wilson; Khairiel Anwar; Febria Suryani; Zaki Ahmad (Scientia Psychiatrica, 2025)
Introduction: The Indonesian archipelago sits at the forefront of the climate crisis, yet the intersection of heat stress and mental health in this equatorial region remains under-researched. Unlike temperate climates, where heatwaves are sporadic, Indonesian cities face a chronic thermal load exacerbated by the Urban Heat Island effect. Methods: We conducted a retrospective ecological time-series analysis in Jakarta, Indonesia, spanning the period from January 1st, 2014, to December 31st, 2024. Daily psychiatric Emergency Department admissions (Total N = 48,210) were aggregated from three referral hospitals. We utilized a Distributed Lag Non-linear Model combined with a quasi-Poisson regression to correlate admissions with meteorological data from the Indonesian Agency for Meteorology, Climatology, and Geophysics, adjusting for holidays, day of the week, and particulate matter 2.5. Results: The Thermal Distress Threshold was identified at a Wet Bulb Globe Temperature of 29.8°C, reflecting a high degree of physiological acclimatization. Beyond this tipping point, the cumulative Relative Risk for acute psychiatric episodes rose to 1.21 (95% Confidence Interval: 1.14–1.29) at lag 0–3 days. Schizophrenia spectrum disorders showed the highest vulnerability (Relative Risk = 1.26) during the transition season heat spikes. Conclusion: The study establishes a localized thermal threshold for psychiatric emergencies in Indonesia. The findings suggest that high ambient humidity, characteristic of the Indonesian climate, significantly amplifies the psychiatric risk of heat. These results necessitate the integration of psychiatric protocols into the BPJS Kesehatan national health strategy for climate adaptation.